Data management with PMS in hotel industry - Mohideen Moyeenudin, Hussam; Javed Parvez, Shaik; Anandan, R; Narayanan, Kumar (International Journal of Engineering and Technology, 2018)
The rapid growth of hotel industry has increased the usage of data with the help of property management system (PMS). It deals with sharing information in a systematic procedure within the organization. The major benefit of data management with PMS is the information can be easily stored and shared between staff members; it is useful during recruitment and when an employee goes on vacation, gets sick, or leaves the organization, It comprise with procedure of work, duties and responsibilities, initiatives, performance, documentation, forming business strategies and systems which enhance the organization. Data management helps in storing the data for handling plans and on methods of executing and developing policies for various situations in hotel. Data Management is a way of managing knowledge base and making it accessible for specific purposes in any industry, also to improve the quality of performance and standards, by various methods of data application in Management practices which involves in understanding the industry and effectively utilizing data in learning and implementing policies of an organisation. This article describes about how Data Management in hotels works with property management system (PMS) and the advantages of having PMS in hotel Industry. This paper also focuses on the advancement in PMS with cloud technology for future demands.